Obelia racemosa Fraser 1941 - Calder, Dale R.; Choong, Henry H. C. (Zenodo, 2018)
? Obelia racemosa Fraser, 1941b ? Obelia racemosa Fraser, 1941b: 82, pl. 15, fig. 7. Holotype : USNM 4883: Canada, Nova Scotia, Western Bank, 91–119 m, 0 7 June 1880, schooner Mist , one colony, 25 cm high (Fraser 1941b), in poor condition, gonophores not seen, labelled “ syntype ”; ethanol. Type locality. Canada, Nova Scotia: Western Bank off Cape Breton Island, 50–65 fm (91–119 m) (Fraser 1941b). Current status. Species inquirenda . Remarks. In being designated as the “ type ”, material of Obelia racemosa at the NMNH (USNM 4883) was fixed as the name-bearing type of the species by Fraser (1941b). Although listed as a syntype in the online database, the specimen count is given as “1.” Fraser’s (1941b) original account of the species implies that it was based on a single specimen, as his description began with the words “Colony large….” The type examined here, consisting of one colony and a few fragments of it, is considered the holotype. Obelia racemosa has not been reported again. The holotype specimen is in poor condition, with no hydranths, little or no coenosarc, and few hydrothecae. Gonosomes were lacking in Fraser’s (1941b) hydroid, and he assigned the species to Obelia Péron & Lesueur, 1810 with question. From his description and illustration, and from the type specimen, however, we consider that generic assignment to be correct. The principal distinguishing characters of O. racemosa appear to be: (1) the stiff racemes formed by distal branchlets and pedicels, and (2) the densely clustered arrangement of the hydrothecae. Although regarded as a synonym of O. dichotoma (Linnaeus, 1758) in WoRMS, O. racemosa somewhat resembles O. plicata Hincks, 1868 in its strongly polysiphonic colony form. The latter species too, however, is considered identical with O. dichotoma in the current WoRMS list, likely following Cornelius (1990, 1995). Its general mode of branching is similar to O. longissima (Pallas, 1766), but the hydrocaulus of that species is usually monosiphonic. Further study is needed to explore the ...